Deep tubewell use is associated with increased household microbial contamination in rural Bangladesh: Results from a prospective cohort study among households in rural Bangladesh. (1st May 2023) - Goel, Varun; Chan, Brianna; Ziade, Mia; Yunus, Md.; Ali, Md. Taslim; Khan, Md. Al Fazal; Alam, Md. Nurul; Faruque, ASG; Babu, Shahabuddin; Kabir, Md.Masnoon; Delamater, Paul L.; Serre, Marc; et al.
Abstract: Deep tubewells are important sources of arsenic mitigation in rural Bangladesh. Compared to commonly available shallow tubewells, deep tubewells tap into deeper low-arsenic aquifers and greatly reduce exposure to arsenic in drinking-water. However, benefits from these more distant and expensive sources may be compromised by higher levels of microbial contamination at point-of-use (POU). This paper examines differences in microbial contamination levels at source and POU among households using deep tubewells and shallow tubewells, and investigates factors associated with POU microbial contamination among deep tubewell users. We assessed a prospective longitudinal cohort of 500 rural households in Matlab, Bangladesh, across 135 villages. Concentration of Escherichia coli ( E. coli ) in water samples at source and POU using Compartment Bag Tests (CBTs) was measured across rainy and dry seasons. We employed linear mixed-effect regression models to measure the effect of different factors on log E. coli concentrations among deep tubewell users. CBT results show that log E. coli concentrations are similar at source and at POU during the first dry and rainy season, but are significantly higher at POU among deep tubewell users during the second dry season. Log E. coli at POU among deep tubewell users is positively associated with both presence (exponentiated beta exp ( b ) = 2.52, 95% Confidence Interval (CI) = 1.70, 3.73) and concentration of E. coli (exp( b) = 1.36, 95% CI = 1.19, 1.54) at source, and walking time to the tubewell source (exp( b) = 1.39, 95% CI = 1.15, 1.69). Drinking-water during the second dry season is associated with reduced log E. coli (exp( b) = 0.33, 95% CI = 0.23, 0.57) compared to the rainy season. These results suggest that while households that use deep tubewells have lower arsenic exposure, they may be at higher risk of consuming microbially contaminated water compared to households that use shallow tubewells. Graphical abstract: Image 1 Highlights: Deep tubewell use may increase domestic drinking-water microbial contamination risk. Deep tubewell (DTW) users often use non-private sources and walk longer to source. Source contamination exacerbates point-of-use contamination among DTW users. Rainy season and longer time to source increases contamination risk among DTW users.